A Descriptive Study of Knowledge, Iron Supplementation Compliance, and Nutritional Status among Adolescent Girls at SMP Negeri 4 Probolinggo - Imandita Tri Oktafiansah; Nur Hatijah; Ani Intiyati; Nuning Marina Pengge (Journal of Nutrition Explorations, 2025)
Anemia remains a significant nutritional problem among adolescent girls, influenced by poor dietary habits, inadequate knowledge, and low compliance with iron supplementation. This study aimed to describe the levels of knowledge, compliance with iron tablet consumption, and nutritional status among adolescent girls. A descriptive study was conducted at SMP Negeri 4 Probolinggo involving 55 eighth-grade female students selected through proportional sampling. Data were collected using validated questionnaires and anthropometric measurements, then analyzed descriptively. Results showed that most respondents were 14 years old (83.6%) and had good to moderate knowledge about anemia (90.9%). However, only 16.4% complied with iron tablet consumption. Nutritional assessment showed that 58.2% had normal BMI-for-age, while 30.9% were undernourished. These findings reveal a gap between knowledge and behavior, emphasizing the need to strengthen school-based nutrition education and iron supplementation programs to prevent anemia in adolescent girls.